Generating new telehealth services using a whole of community approach: experience in regional Queensland. (October 2014) - Smith, Anthony C; Caffery, Liam J; Saunders, Ruth; Bradford, Natalie K; Gray, Leonard C
We implemented a community telehealth project in the three towns in the Darling Downs area of Queensland over a 2-year period starting in July 2012. The purpose of the project was to generate telehealth activity in hospitals, general practice and selected residential aged care facilities. Telehealth education and training was provided to clinicians in the three towns and a community awareness campaign was delivered using advertisements in newspapers, messages in social media and presentations at community events. A total of 55 stakeholders were engaged with during 61 site visits to health care facilities during the first two years of the project. During the study period, telehealth activity in Queensland increased in the hospital sector by 39% and in the non-hospital sector by 99%. In the Darling Downs region, telehealth activity in the hospital sector increased by 104%, compared to 28% in the rest of Queensland. However, in the non-hospital sector, the increase in telehealth activity in the Darling Downs region was similar to the rest of Queensland. Telehealth services established and/or facilitated by the project included specialist geriatric ward rounds in Dalby, Chinchilla and Miles for patients in the local hospitals and nursing homes; and ad-hoc teleconsultations for children and adults living in these communities, with specialists at Toowoomba and hospitals in Brisbane. An increase in telehealth implies better access to a range of clinical services, which may result in improved clinical outcomes for patients.